EXPERT SYSTEM FOR DIAGNOSIS OF AIRBORNE INFECTIOUS DISEASES IN HUMANS WITH MAMDANI FUZZY LOGIC - Subekti, Dayat; Priyanto, Agung; Mukti, Agung Permana; Azzuhry, Dimas Rully (JUTEKIN (Jurnal Teknik Informatika), 2023)
People in today's information age are increasingly demanding all kinds of information to be presented quickly. One of them is information in the medical field, in this case information about the diagnosis of a disease which is usually in the form of an expert system. Various methods are used in expert systems, one of which is Mamdani fuzzy logic or better known as the Mamdani inference system. The use of fuzzy logic in diagnosing this disease does not require numbers as input.The Mamdani fuzzy logic expert system in this study is specifically used to diagnose infectious diseases in humans, namely: whooping cough or pertussis, measles, diphtheria, mumps, meningitis, tuberculosis, variola, and varicella. This system diagnoses diseases based on inputting the characteristics or symptoms suffered. The diagnosis result is a number of possible diagnoses for each disease. The closer the number to 1 (one), the higher the probability of contracting one of the diseases mentioned above.The system that has been created can already be used to detect diseases according to the characteristics or symptoms entered. However, this system is only a research and the results cannot be used as a reference for real disease diagnosis.